1978
DOI: 10.1002/ijc.2910220304
|View full text |Cite
|
Sign up to set email alerts
|

Primary epstein‐barr virus infections in african infants. I. Decline of maternal antibodies and time of infection

Abstract: Thirty-one infants living in Accra, Ghana, an area endemic for Burkitt's lymphoma, were visited a t monthly intervals for the f i r s t 15 months of life and once again a t 21 months. Sera obtained a t each visit were tested for antibodies t o EpsteinBarr virus (EBV) capsid antigen (VCA), EBVinduced early antigens (EA) and EBV-associated nuclear antigen (EBNA) by immunofluorescence techniques as well as for EBV-neutralizing antibodies and antibody-dependent cell-mediated cytolysis. A l l infants had maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 18 publications
(13 reference statements)
7
73
2
Order By: Relevance
“…This pattern has also been observed in other studies and is due to preexisting maternal antibodies active in infants under six-months-old (Leogrande et al, 1993). Longitudinal serological data have shown that maternal anti-EBV protection usually lasts for 3-4 months (Biggar et al, 1978;Chan et al, 2001). Once the level of maternal antibodies declines, infants begin to seroconvert.…”
Section: Discussionsupporting
confidence: 83%
“…This pattern has also been observed in other studies and is due to preexisting maternal antibodies active in infants under six-months-old (Leogrande et al, 1993). Longitudinal serological data have shown that maternal anti-EBV protection usually lasts for 3-4 months (Biggar et al, 1978;Chan et al, 2001). Once the level of maternal antibodies declines, infants begin to seroconvert.…”
Section: Discussionsupporting
confidence: 83%
“…One important eBL co-factor, Epstein-Barr virus infection, is evenly distributed in the population and infection occurs early in childhood. 21,22 Our consistent findings, therefore, may imply clustering of other environmental or socio-cultural eBL co-factors, although potential reporting bias must also be assessed. Neither high-risk cluster included administrative units in Siaya District, as initially hypothesized.…”
Section: Spatial Clusteringmentioning
confidence: 79%
“…Clinically, elevated levels of anti-VCA and anti-EBNA1 immunoglobulin G (IgG) antibodies have been used as evidence of past infection (9), while the presence of IgG antibodies to the EBV early antigens (EAd and Zta) generally reflects recent or reactivated infections (10,11). Although EBV-specific antibody patterns reflect the dynamics of EBV activity in adults, few studies have addressed this issue in infants and children (3,(12)(13)(14)(15) or in newborns (16,17). More importantly, no comparison to maternal antibody levels has been made and there has been no analysis of how maternal malaria infections impact transplacental transfer of EBV-specific antibodies.…”
mentioning
confidence: 99%